COUNSELING SERVICE ASSISTANCE IN PSYCHOLOGICAL RECOVERY OF DOMESTIC VIOLENCE VICTIMS IN UPTD PPA SAMARINDA CITY - NANIK SURYATI; ABUBAKAR IDHAM MADANI; RUDY HADI KUSUMA (Universitas Islam Negeri Mataram, 2023)
Domestic violence cases are still rampant among the community, especially women and children, which causes disruption to the psychological condition of victims. UPTD PPA Samarinda City as a forum for handling victims of violence provides counseling assistance to restore the psychological condition of victims of domestic violence. This study aims to determine the implementation of counseling services in the psychological recovery of victims of domestic violence at UPTD PPA Samarinda City. This research uses a qualitative approach with data collection through interviews and observations. The results showed that forms of domestic violence affect the psychological condition of victims so that counseling services play an important role in the psychological recovery of victims. There are several types of counseling services provided for handling victims of domestic violence, including individual counseling, family counseling, and marriage counseling.